Cultural diplomacy and internationalism in regional art institutions. Issue 4 (2nd October 2019) - Walden, Lauren
Abstract : This study posits that current cultural diplomacy practice in UK museums and galleries could be significantly improved. Indeed, cultural diplomacy is commonly viewed as nationalist propaganda. An attempt to theoretically debunk this proposition indicates that greater understanding between peoples can be engendered by unifying the ideologies of internationalism and liberalism in the cultural sector. Liberalism is viewed as the present ideology operating in Museums and Galleries whilst internationalism is considered as a nascent force. Working in symbiosis, liberalism allows for a multiplicity of discourse whilst internationalism allows for a critical reappraisal of the status quo and nation-state hegemony. Indeed, a multiplicity of dialogic discourse is essential for cultural institutions to maintain a non-hegemonic stance. This is, of course, particularly apparent in contemporary art work which can often be subversive of national governments and the very idea of a nation-state. Further to this, a form of localised cultural diplomacy can reach the public at large and question the cultural capital of world centres. Empirically speaking, the exhibition format is used as a means to render cultural diplomacy palatable for public consumption. Hence, the UK case study Art from Elsewhere will be introduced which has rendered the international a normative presence in local art galleries. This 2014–2016 exhibition comprised a tour of recent contemporary art acquisitions in regional permanent collections which were funded by a £5 million pound grant from the UK charitable organisation, Art Fund. Instead of monophonic exhibitions emanating from one nation, Art from Elsewhere engenders a multilateral dialogue catalysed by the polyphonic nature of artists from several different nations whose works are juxtaposed both in conflict, symmetry and contrast to one another.